Geriatric impairments are prevalent and predictive of survival in older patients with cancer receiving radiotherapy: a prospective observational study. (3rd April 2022) - Eriksen, Guro Falk; Šaltytė Benth, Jūratė; Grønberg, Bjørn Henning; Rostoft, Siri; Kirkhus, Lene; Kirkevold, Øyvind; Hjelstuen, Anne; Slaaen, Marit
Abstract: Background: A systematic assessment of problems that are frequent in older age (geriatric assessment [GA]) provides prognostic information for patients undergoing cancer surgery and systemic cancer treatment. We aimed to investigate the prevalence of geriatric impairments and their impact on survival in older patients with cancer receiving radiotherapy (RT). Material and methods: A single-centre prospective observational study was conducted including patients ≥65 years referred for curative or palliative RT. Prior to RT, we performed a modified GA (mGA) assessing comorbidities, medications, nutritional status basic- and instrumental activities of daily living (IADL) mobility, falls, cognition and depressive symptoms. Impairments in each mGA domain were defined. Overall survival (OS) was presented by Kaplan Meier plots for groups defined according to the number of impairments, and compared by log-rank test. The association between mGA domains and OS was assessed by Cox proportional hazard regression analysis. Results: Between February 2017 and July 2018, 301 patients were included, 142 (47.2%) were women. Mean age was 73.6 (SD 6.3) years, 162 (53.8%) received curative RT. During the median observation time of 24.2 months (min 0.3, max 25.9), 123 (40.9%) patients died. In the overall cohort, 49 (16.3%) patients had no geriatric impairment, 81 (26.9%) had four or more. OS significantly decreased with an increasing number of impairments ( p < .01). Nutritional status (HR 0.90, 95% CI [0.81; 0.99], p = .038) and IADL function (HR 0.98, 95% CI [0.95; 1.00], p = .027) were independent predictors of OS. Conclusion: Geriatric impairments were frequent among older patients with cancer receiving RT and nutritional status and IADL function predicted OS. Targeted interventions to remediate modifiable impairments may have the potential to improve OS. Trial registration: Cinicaltrials.gov ID:NCT03071640.